Controle biológico de "Cylindrocarpon" sp. e fusarium sp. em porta-enxertos de videira utilizando Bacillus sp. - Russi, Alessandra (My University, 2019)
The Brazilian viticulture has been expanding to different regions and standing out in the national economy. Despite significant advances in recent years, the culture has suffered serious problems with reduced productivity, decline and young death of vines. Many factors are involved in the grapevine decline including soil and crop management, abiotic stresses, pests, viral and fungal diseases. In this context, phytopathogenic fungi are considered the main responsible for damage to the crop and for the need to replant vineyards. Therefore, the use of propagative material with agronomic, physiological and phytosanitary quality is essential. However, healthy plant material may be reinfected when subjected to adverse environmental conditions, such as soils contaminated with phytopathogens. The present study aimed to evaluate the potential of Bacillus sp. strain F62 in the in vitro and in vivo biocontrol of Fusarium sp. and “Cylindrocarpon” sp. These phytopathogens cause serious diseases on grapevine and have been the subject of studies in many wine regions in the world, especially “Cylindrocarpon” sp., which causes black-foot on grapevine. In vitro experiments consisted of the evaluation of the antagonism by volatile and diffusible compounds (paired culture), as well as, the evaluation of the inhibition of conidial germination. In vivo experiments were performed on cuttings and on micropropagated grapevine rootstocks 1103P and SO4, under greenhouse conditions. In the paired culture assay, the bacterium inhibited the mycelial growth of five isolates of “Cylindrocarpon” sp., ranging from 61.09% a 69.98% and four isolates of Fusarium sp., ranging from 35.35% to 63.62%. In antagonism assay by volatile compounds there was no significant difference in relation to the control for both phytopathogens. Regarding the germination of conidia, it was verified that the bacterial suspension and the filtrate metabolites were effective in inhibiting the germination of fungal spores. In the in vivo experiment in cuttings of 1103P, unlike the cuttings of SO4, no statistically significant difference in growth promotion was verified in relation to the control. However, Bacillus sp. F62 reduced the percentage of re-isolation of “Cylindrocarpon” sp. to 27.9% in SO4 and 10.3% in 1103P, in relation to the control. Preventive treatment with Bacillus sp. F62 also reduced the percentage of re-isolation of Fusarium sp. to 17.6% in SO4. Micropropagated rootstocks treated with Bacillus sp. F62 was found to have greater vigor and better vegetative development compared to control. The rhizobacteria reduced the incidence of Fusarium sp. in 52.4% in micropropagated rootstock SO4. In addition, Bacillus sp. reduced the incidence of “Cylindrocarpon” sp. in 36.0% on micropropagated plants of SO4 and Paulsen 1103. In summary, Bacillus sp. F62 was effective in the in vitro and in vivo biocontrol of Fusarium sp. and “Cylindrocarpon” sp. and also stimulated the growth and development of micropropagated plants of both grapevine rootstocks evaluated in this study. [resumo fornecido pelo autor]
A viticultura brasileira vem se expandindo para diferentes regiões e destacando-se no cenário econômico nacional. Apesar dos significativos avanços ocorridos nos últimos anos, a cultura tem sofrido sérios problemas com a redução da produtividade, declínio e morte precoce de videiras. Muitos são os fatores envolvidos no declínio da videira incluindo o manejo do solo e da cultura, estresses abióticos, ocorrência de pragas, doenças virais e fúngicas. Nesse contexto, os fungos fitopatogênicos são considerados os principais responsáveis pelos danos ocasionados à cultura e pela necessidade de reconversão de vinhedos. Sendo assim, torna-se essencial a utilização de mudas com qualidade agronômica, fisiológica e fitossanitária. Contudo, mudas sadias podem ser reinfectadas quando submetidas a condições ambientais adversas, tais como solos contaminados com fitopatógenos. O presente estudo teve como objetivo avaliar o potencial de Bacillus sp. linhagem F62 no biocontrole in vitro e in vivo de Fusarium sp. e “Cylindrocarpon” sp., visto que ambos são causadores de sérias doenças na videira e têm sido objeto de estudos em diferentes regiões vitivinícolas no mundo, com destaque para “Cylindrocarpon” sp., causador do pé-preto na videira. Os ensaios in vitro consistiram na avaliação do antagonismo por compostos voláteis e compostos difusíveis (cultivo pareado), bem como, na avaliação da inibição da germinação de conídios. Os ensaios in vivo foram realizados em estacas e em mudas micropropagadas dos porta-enxertos de videira Paulsen 1103 e SO4, em casa de vegetação. No ensaio de cultivo pareado, a bactéria inibiu o crescimento micelial de cinco isolados de “Cylindrocarpon” sp., variando de 61,09% a 69,98% e de quatro isolados de Fusarium sp. variando de 35,35% a 63,62%. No ensaio de antagonismo por compostos voláteis não houve diferença significativa em relação ao controle para ambos os fitopatógenos. Em relação à germinação de conídios, verificou-se que tanto a suspensão bacteriana quanto o filtrado da cultura foram eficazes na inibição da germinação de esporos fúngicos. No experimento in vivo em estacas de Paulsen 1103, diferentemente das estacas de SO4, não foi verificada diferença estatisticamente significativa na promoção do crescimento em relação ao controle. No entanto, Bacillus sp. F62 reduziu o percentual de reisolamento de “Cylindrocarpon” sp. para 27,9% em SO4 e 10,3% em Paulsen 1103, em relação ao controle. O tratamento preventivo com Bacillus sp. F62 reduziu, ainda, o reisolamento de Fusarium sp. para 17,6% em SO4. Em mudas micropropagadas de ambos os porta-enxertos tratadas com suspensão de Bacillus sp. F62 foi verificado maior vigor e melhor desenvolvimento vegetativo em relação ao controle. A rizobactéria reduziu o percentual de reisolamento de Fusarium sp. em 52,4% em mudas micropropagadas de SO4. Além disso, Bacillus sp. F62 reduziu o percentual de reisolamento de “Cylindrocarpon” sp. em 36,0%, em mudas micropropagadas de SO4 e Paulsen 1103. Conclui-se que Bacillus sp. F62 foi eficaz no biocontrole in vitro e in vivo de Fusarium sp. e “Cylindrocarpon” sp., além de estimular o crescimento e o desenvolvimento de mudas micropropagadas de ambos os porta-enxertos de videira avaliados neste estudo. [resumo fornecido pelo autor]
Keywords: Uvas - Cultivo; Fitopatologia; Fungos - Controle biológico; Bactérias; Viticulture; Plant diseases; Fungi - Biological control; Bacteria